PRAKTIK PENGANGGARAN PARTISIPATIF DALAM PEMANFAATAN DANA DESA DI KECAMATAN BRATI KABUPATEN GROBOGAN - Wildansyah Firdaus Adiguna; Novia Arismawati (JURNAL LITBANG PROVINSI JAWA TENGAH, 2020)
National development is the government effort in achieving prosperity for the community who live in a city or a village. National development done from the smallest unit is developing village. The government stimulates rural development by Village Funds Allocation (ADD) and Village Funds. In this development context, community participation is needed. An example of the community involvement is giving some relevant suggestion related to budgeting and programming. The aim of this research is to explain the practices of community participation at each stage of budgeting for village development. The villages in the Sub District of Brati, the Regency of Grobogan is the research taken place. The method used in this study is a qualitative method performed by providing interpretation of the data obtained. The steps undertaken in this analysis starting with data reduction, data presentation with charts and text and then drawn some conclusions. Based on the results of the analysis, it can be concluded that the practice of participatory budgeting in the using of village funds in Brati Sub District was still less than the maximum by involving the community, especially at the budgeting stage.